Quantitative estimation of TV white space in Southwest Nigeria - Ilesanmi Banjo Oluwafemi; Ayodeji Peter Bamisaye; Matthew Adedeji Faluru (Universitas Ahmad Dahlan, 2021)
The demand for bandwidth has increased in recent years with the advent of new technologies in the wireless systems which have resulted into spectrum crunch. Utilizing the free ultra high frequency (UHF), television (TV) channels also known as TV white space (TVWS) has been proposed as a strategy for increasing spectral efficiency. Deploying TVWS requires the knowledge of the estimate of the available TVWS. In this paper, a quantitative estimation of the available TVWS in South West, Nigeria is computed using the protection view point approach, the pollution viewpoint approach and the Federal Communication Commission (FCC) rule. Results from the estimation shows that the pollution view point approach will guarantee enough protection from the primary users and hence prevent interference from the secondary users. The findings also reveal that there are abundant TVWS in the considered states for the deployment of TVWS devices.